2021
DOI: 10.3389/fphar.2020.566401
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Immunotherapies to Improve Anticancer Immunity

Abstract: Checkpoint inhibitors are widely used immunotherapies for advanced cancer. Nonetheless, checkpoint inhibitors have a relatively low response rate, work in a limited range of cancers, and have some unignorable side effects. Checkpoint inhibitors aim to reinvigorate exhausted or suppressed T cells in the tumor microenvironment (TME). However, the TME contains various other immune cell subsets that interact to determine the fate of cytotoxic T cells. Activation of cytotoxic T cells is initiated by antigen cross-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 205 publications
0
7
0
Order By: Relevance
“…Both Paclitaxel and blockade of IL-8Rs were separately used in melanoma therapy, so such a combinatorial would be expected successful in melanoma too. Additional chemotaxis inhibitors, as those targeting CXCR2, an important marker for neutrophil migration from bone marrow into site of inflammation, in combinations withother inhibitors of CKs/CKRs (e.g., CXCL12/CXCR4 or CCR5-maraviroc) are under investigation to hinder the recruitment of neutrophils to the TME [ 212 , 213 ]. TAMs —Numerous studies showed that TAMs which favor tumor progression resemble to macrophage M2 phenotypes [ 214 ].…”
Section: Interleukin 8—a Major Key-player In CM Pathogenesismentioning
confidence: 99%
“…Both Paclitaxel and blockade of IL-8Rs were separately used in melanoma therapy, so such a combinatorial would be expected successful in melanoma too. Additional chemotaxis inhibitors, as those targeting CXCR2, an important marker for neutrophil migration from bone marrow into site of inflammation, in combinations withother inhibitors of CKs/CKRs (e.g., CXCL12/CXCR4 or CCR5-maraviroc) are under investigation to hinder the recruitment of neutrophils to the TME [ 212 , 213 ]. TAMs —Numerous studies showed that TAMs which favor tumor progression resemble to macrophage M2 phenotypes [ 214 ].…”
Section: Interleukin 8—a Major Key-player In CM Pathogenesismentioning
confidence: 99%
“…Tumor-infiltrating NK cells exhibit poor cytotoxic capacity, accompanied by downregulation of activating receptors, upregulation of inhibitory receptors, and upregulation of immune checkpoint receptors, compared with NK cells from healthy tissues (103). The development of novel approaches such as monoclonal antibodies (mAbs) to block inhibitory receptors enhances NK cell function and its anti-tumor capacity (104). Despite efforts to combat immunosuppressive effects, multiple factors in the TME still limit NK cell function.…”
Section: Tme Suppressive Factorsmentioning
confidence: 99%
“…In recent years, ICIs have made revolutionary breakthroughs in the treatment of a variety of advanced solid tumors [ 1 , 2 ]. However, studies have found that the inhibition rate of ICIs in solid tumors is only 10%–40% [ 3 , 4 ], which indicates that a large number of patients cannot benefit from immunotherapy. In addition, ICIs technology has been stagnant in the area breast cancer treatment, because breast cancer was previously considered to be a "cold tumor" with low immunogenicity [5] .…”
Section: Introductionmentioning
confidence: 99%